Cultura de engenho de cana na Paraíba: em torno de uma sociologia da cachaça - Barbosa, José Luciano Albino (2010)
This research consists of a study about the process of changing in the alembic cachaça productive sector in Paraiba from the 90 s. From a drink that was historically considered as marginal to one that achieved great distinction in the country and in the new drink triers, the distilled drink from Paraíba suffered a concept changing which symbolically remade it, according to publicity and modernizing productive apparatus. The tradition destruction that used to collect the cachaça and put it in old wood containers and colonial mills, which were referred by José Lins do Rego, is part of the dynamic history of creating, in this perspective, a new tradition, a hybrid drink, made in mills, bottles, labels and brands, but still with old symbols, with the genuine and traditional mill image, which now receives different adjectives, as it became a touristic point, but that keeps memories and new quality cachaça producers. From the mills selection to the case study it was created an ethnografic investigation, from the everyday perception to the actions register that dynamize them. During the moonshine production, the mills create culture and identity place: the diferent drink triers of the cachaça from Paraíba, the typical cachaceiro (associated to the alcoholism and failure image), the paraibana cachaça of the interprising farm owner and that was open to changes that do not let the slavery past define his profile, that delineates, through the new social actors, a new sugar cane cycle in the country. This modernizing era is an illusion set of the cachaça, that attracts revelers with costumes related to Apollo, control and refinning in beautiful and small bottles that save the aphrodisiac liquid. In a growing market, according to the producers evaluation, the drinking desire or the desire to try the amalgam production and comsuption in a new aesthetic cachaça.